Dialogic discussions for enhancing children’s argumentation skills in Indonesian reading sessions - Diana Purwaningrum (Indonesian Journal of Applied Linguistics)
Dialogic discussions offer advantages in improving language and literacy skills. However, research in the Indonesian context on this topic is limited. Furthermore, existing studies also tend to overlook the challenges associated with children’s interactions. To bridge this research gap, this study investigated the role of dialogic discussions in advancing children’s argumentation abilities during Indonesian reading sessions. This study utilized a case study approach, involving sixteen fourth-grade children from a public elementary school. Data were collected through observations, field notes, and audio recordings. The children participated in small group discussions during six reading sessions. These sessions involved exploring both Indonesian fiction and non-fiction texts, centered on significant moral or social questions and dilemmas. The findings revealed an increased use of various argumentation strategies by the children, including presenting reasons, posing challenges, and responding to challenges. Using personally engaging texts proved beneficial for sustaining discussions, as it encouraged children to share their lived experiences and opinions. However, the findings also indicated that children who did not participate seemed distracted during individual tasks. The study provides valuable insights into the dynamics and complexities of small group discussions during Indonesian reading sessions.